2017
DOI: 10.1016/j.cub.2016.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Geometry Aligns the Hippocampal Map during Spatial Reorientation

Abstract: Summary When a navigator's internal sense of direction is disrupted, she must rely on external cues to regain her bearings, a process termed spatial reorientation. Extensive research has demonstrated that the geometric shape of the environment exerts powerful control over reorientation behavior, but the neural and cognitive mechanisms underlying this phenomenon are not well understood. Whereas some theories claim that geometry controls behavior through an allocentric mechanism potentially tied to the hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 49 publications
14
95
0
Order By: Relevance
“…While some comparisons produced results consistent with these predictions, in most cases we found that mice utilized a coherent map: a configuration of place fields that maintain the same angle and distance from one another. Consistent with recent studies [14,15], however, we found that coherent maps frequently rotated in a manner that does not utilize specific arena cues or larger room cues for orientation. Maps were flexible as mice frequently employed a coherent map between the two different arenas while simultaneously modulating activity in a subset of cells to discriminate between them.…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…While some comparisons produced results consistent with these predictions, in most cases we found that mice utilized a coherent map: a configuration of place fields that maintain the same angle and distance from one another. Consistent with recent studies [14,15], however, we found that coherent maps frequently rotated in a manner that does not utilize specific arena cues or larger room cues for orientation. Maps were flexible as mice frequently employed a coherent map between the two different arenas while simultaneously modulating activity in a subset of cells to discriminate between them.…”
Section: Introductionsupporting
confidence: 91%
“…As noted in the introduction, instability observed in previous studies during random foraging [18,19] could result from global remapping of place fields (Figure 2A, top). Alternatively, we hypothesized that the trial-by-trial rotations of place fields observed in a recent study [14] might persist over longer time scales (Figure 2A, bottom). In agreement with this study, we likewise found that place fields frequently rotated together coherently between sessions by maintaining the same distance and angle from each other (Figure 2C–D).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations